2009
DOI: 10.1007/s10689-009-9257-5
|View full text |Cite
|
Sign up to set email alerts
|

A high frequent BRCA1 founder mutation identified in the Greenlandic population

Abstract: Approximately 10% of all breast and ovarian cancers are dominantly inherited and mutations are mainly found in the BRCA 1 and 2 genes. The penetrance of BRCA1 mutations is reported to be between 68 and 92% and confers a 36-92% life time risk of breast cancer. Most mutations in BRCA1 are uniquely occurring mutations, but founder mutations have been described. In this study we describe a founder mutation with wide spread presence in the Inuit population. We have screened 2,869 persons from Greenland for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Most mutations in BRCA1 are uniquely occurring mutations, but a specific founder mutation in Greenlandic Inuit has been found and described in two different studies (11,12). Founder mutations appear in the DNA of one or more individuals who are founders of a distinct population.…”
Section: Ad 2: Genetic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most mutations in BRCA1 are uniquely occurring mutations, but a specific founder mutation in Greenlandic Inuit has been found and described in two different studies (11,12). Founder mutations appear in the DNA of one or more individuals who are founders of a distinct population.…”
Section: Ad 2: Genetic Susceptibilitymentioning
confidence: 99%
“…These mutations occur all over the world and in Greenland a specific founder mutation has been identified. Recent studies have shown a high frequency of this BRCA1 founder mutation, especially at the East coast of Greenland with the highest population frequency of a BRCA1 mutation ever described (11,12). These findings suggest that genetics is a potential risk factor associated to the risk of developing BC in Inuit women in certain parts of Greenland.…”
mentioning
confidence: 99%
“…The prevalence of BRCA1 and BRCA2 mutations combined is approximately 0.3% in North America (1217), but may be higher than this in countries or populations where there are founder mutations, such as Israeli Jews (1820), Dutch (21), French-Canadians (22), Icelandic (23), Greenlandic (24), Polish (25), Russia and Eastern European (2630) and Greek populations (3132). Recurrent mutations have also been described in women of Hispanic origin in the United States (3338).…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of all breast and ovarian cancers are dominantly inherited mainly by mutations in the BRCA1 and BRCA2 genes. Harboe et al (169) found three patients out of nine with ovarian cancer (33%), and one out of 10 breast cancer patients (10%) carrying the BRCA1 mutation in Greenland. Risk of prostate cancer in Inuit is 10–20% of the risk in the respective national white population (161,170).…”
Section: Contaminant Exposure and Cancer Risk In Arctic Regionsmentioning
confidence: 99%